Disposable immunosensor for human cardiac troponin T based on streptavidin-microsphere modified screen-printed electrode - Silva, Barbara V. M.; Cavalcanti, Igor T.; Mattos, Alessandra B.; Moura, Patricia; Sotomayor, Maria Del Pilar Taboada [UNESP]; Dutra, Rosa F. (Elsevier Advanced Technology, 2010)
Screen-printed electrodes (SPE) have been widely used in the design of disposable sensors bringing advances in the use of electrochemical immunosensors for in field-clinical analysis. In this work, streptavidin polystyrene microspheres were incorporated to the electrode surface of SPEs in order to increase the analytical response of the cardiac troponin T (cTnT), a specific biomarker for the acute myocardial infarction diagnosis. The precise calculation of the stoichiometric streptavidin-biotin ratio [1:4]allowed the increase of sensitivity and stability of the immunosensor response to the cTnT analyte. The surface of the immunosensor was characterized by scanning electron microscopy and cyclic voltammetry. It was observed that the use of streptavidin microspheres significantly increased the analytical sensitivity of the electrode in 8.5 times, showing a curve with a linear response range between 0.1 and 10 ng mL(-1) of cTnT and a detection limit of 0.2 ng mL(-1). The proposed SPE showed ease preparation and high sensitivity allowing the detection of cTnT in the range of clinical levels. The new device coupled with a portable electrochemical analyzer shows great promise for point-of-care quantitative testing of necrosis cardiac proteins. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Immunosensor; Screen-printed electrode; Myocardial infarction; Troponin T